Pyrocarbon Lunate Arthroplasty: An Option for the Young Patient with Advanced Kienbock Disease - Dwivedi, Shashank S.; Chung, Kevin C. (Seminars in Plastic Surgery, 2024)
Kienbock disease, or avascular necrosis of the lunate, is an uncommon cause of a painful and stiff wrist. Management options range from conservative treatment in the form of immobilization and corticosteroid injections to a wide variety of surgical treatments that depend on the structural integrity of the lunate, intercarpal relationships, and the condition of the articular cartilage of the wrist. A particularly difficult problem lies in the management of young patient in whom vascularized bone grafting of the lunate has failed but in whom arthritis has not yet developed. Pyrocarbon lunate implant arthroplasty is a newer treatment option for such a patient, and allows the preservation of the remainder of the proximal carpal row while directly addressing the degenerative lunate. This article describes the evidence and surgical technique for lunate implant arthroplasty and presents an illustrative case example.
Keywords: Kienbock disease; pyrocarbon; lunate arthroplasty